Wildfowl conservation in Denmark - Matthews, G V T (Wildfowl, 1959)
Denmark’s land area (16,575 square miles) is not much greater than that of the Netherlands which we considered in the last Annual Report. It is not so densely inhabited, the human population being about four and a half millions (as against ten million Dutch), but no less than 110,000 shooting licences are issued each year (as against 20,000 in the Netherlands). Per head of population shooters in Denmark are thus more than twelve times as numerous as in the Netherlands, and some four times as plentiful as in our own country. Small wonder, then that Denmark can claim to be one of the most game-conscious countries in Europe. Land reclamation of the urgent, hungering type we see in the Netherlands is not an important factor and there are no active duck decoys. So the conservation problems are very different in the two countries.